COMPARISON OF THE PERFORMANCE OF WHEAT FLOUR MILLS IN IRAQ FOR THE YEAR 2019 BAGHDAD GOVERNORATE CASE STUDY - Mohammed A.J.A.,; H.J.MOHAMMED, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to compare the performance of flour mills in Baghdad governorate during 2019. A sample of 53 mills were collected, divided into four categories according to their productivity. The technical and economic efficiency were estimated according to the data envelope method with an input oriented. The results showed that the values of the general average of scale efficiency and technical efficiency constant CRS, and variable return to scale VRS for the sample in the first half according to its production capacity of the mills amounted to (0.876, 0.937, 0.937)% respectively. Compared to the results of the second period (0.896, 0.952, 0.941) %, respectively. As for the results of allocative and economic efficiency in the first period, it amounted to (0.0856, 0.803) %, respectively. Compared to the results of the second period (0.0840, 0.801) %, respectively. In summary, we conclude that the increase in the quantities of raw wheat in the second period of the sample by 7.0% resulted in a positive effect on the results of technical efficiency TEvrs, and this was also indicated by the results of the Malmquist index. As for the decrease in the results of the average economic efficiency of the sample in the second period due to the low economic efficiency of the mills of the first category, which negatively affected the results of the sample as a whole. One of the recommendations of the research is to update the four categories of mills’ machines, as it has become a problem in wasting input quantities and mills moving away from optimizing the economic efficiency of those mills. As for the mills of the first category, the levels of production capacities must be raised because the current levels do not serve the flour industry and it negatively affected the average sample efficiency.